2007
DOI: 10.1080/15563650701354168
|View full text |Cite
|
Sign up to set email alerts
|

Development and Implementation of An Emergency Department Observation Unit Protocol for Deliberate Drug Ingestion in Adults – Preliminary Results

Abstract: Although initial numbers are too small for meaningful analysis, the results suggest that prolonged observation of this problematic patient subset within an EDOU is feasible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Modeling after the success of these ''chest pain units,'' other disease processes have also been successfully managed in this expedited manner, including acute asthma exacerbation [17,18], acute decompensated congestive heart failure [19], and atrial fibrillation [20]. Still more presenting complaints being investigated for such expedited evaluation include syncope [21] and overdose [22,23].…”
Section: Discussionmentioning
confidence: 98%
“…Modeling after the success of these ''chest pain units,'' other disease processes have also been successfully managed in this expedited manner, including acute asthma exacerbation [17,18], acute decompensated congestive heart failure [19], and atrial fibrillation [20]. Still more presenting complaints being investigated for such expedited evaluation include syncope [21] and overdose [22,23].…”
Section: Discussionmentioning
confidence: 98%
“…(11) A previous study suggested that up to 25% of ED poisoning ingestions who were cleared for psychiatric evaluation had an inadequate observation period post-ingestion. (16) The proportion of patients being discharged home during normal business hours was significantly increased following the opening of the ESSU. This also most likely reflects a greater proportion being cared for in an inpatient capacity post ESSU opening.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is little information regarding the use and function of short‐stay units in EDs for psychiatric patients, available studies suggest they are suitable for the management of people with deliberate self‐harming behaviours – notably those presenting after overdose who do not require intensive care unit services (Dallos & Mouzas 1981, Ryan et al. 1996, Sztajnkrycer et al. 2007).…”
Section: The Present Papermentioning
confidence: 99%